Important sociocultural aspects of diabetes mellitus in Qatar: A rapidly developing Arab gulf state - Soliman, Ashraf T.; Alali, Maryam; Alzyoud, Mahmoud; Awwa, Ahmed El; Alhumaidi, Noora; Sabt, Aml (Journal of Social Health and Diabetes, 2013)
Socio-cultural factors can profoundly influence diabetes control in diabetic patients. Qatar is an oil-rich country characterized by rapid urbanization. Excessive consumption of fast food, sedentary rich life style with totally air-conditioned housing, luxury cars, servants, and little outdoors activities and exercise due to hot weather most of the year have led to an epidemic of obesity and high prevalence of type 2 DM and negatively interfered with metabolic control. Increased incidence of divorce (around 40%) appears to be a risk factor for repeated diabetic keto-acidosis and poor control in children with type 1 DM. In addition, the high prevalence vitamin D deficiency and its possible depressive effect on insulin secretion may be associated with poor diabetes control.
Keywords: Diabetes mellitus; obesity; sociocultural factors; urbanization